VERTEBRAL HEART SCORES IN EIGHT DOG BREEDS. Issue 1 (21st September 2012) - Jepsen‐Grant, K.; Pollard, R.E.; Johnson, L.R.
<x xml:space="preserve">Abstract</x> The vertebral heart score (VHS) measurement is commonly used to provide a more objective measurement of cardiomegaly in canines. However, several studies have shown significant breed variations from the value previously established by Buchanan and Bücheler (9.7 ± 0.5). This study describes VHS measurements in Pug, Pomeranian, Yorkshire Terrier, Dachshund, Bulldog, Shih Tzu, Lhasa Apso, and Boston Terrier dog breeds. Dogs with two or three view thoracic radiographs, no subjective radiographic evidence of cardiomegaly, and no physical examination findings of heart murmurs or gallop rhythms were included in the study. The Pug, Pomeranian, Bulldog, and Boston Terrier groups were found to have a VHS significantly greater than 9.7 ± 0.5 (P < 0.00001, P = 0.0014, P < 0.0001, P < 0.00001, respectively). Body condition score (BCS) was found to have a significant effect on the VHS of Lhasa Apso group. Anomalous vertebrae in the thoracic column were associated with a significant increase in VHS of the Bulldog (P = 0.028) and Boston Terrier (P = 0.0004) groups. Thoracic depth to width ratio did not have a significant effect on VHS.